Gram+ bacterial microbiota - Yin & Yang of infectious disease - Cleary, P. Patrick (Henry Stewart Talks, 2011)
Important Gram-positive bacterial species, How the human environment influence the Gram + microbiome, Bifidobacterium defends against Gram-negative pathogens, Antibiotic therapy induces disease, Intestine microbiota induced biochemical changes, Fecal transplants cure C. difficile infections, The genetic plasticity of the Gram-positive with regard to disease potential, Gram-positive acquire genes to become pathogens
Updated at 2017/01/31